The Use of Serious Games in Knowledge- and Skills-Based Digital Counselling: Applications to Trafficking in Persons in the War in Ukraine - Haahr, Mads (Springer Verlag, 2023)
This paper presents a serious game designed to help train child helpline counsellors in the detection and response to contacts by children risking conflict-related human trafficking and child sexual abuse and exploitation. It presents trainee counsellors with three stories following young people from Ukraine: Andriy, Olga and Ilya, who contact a child helpline to seek counselling for what are likely situations of trafficking or child sexual exploitation. In each story, the trainee takes on the role of counsellor and interacts with the child character through a branching narrative. The serious game is developed by Haunted Planet Studios and Child Helpline International, in partnership with Terre des Hommes Netherlands as part of their Emergency Ukraine Response, and is currently being tested as part of a larger training curriculum.
Lecture Notes in Computer Science (LNCS)
Joint Conference on Serious Games (JCSG)
Keywords: Serious Games; Games for Learning; Soft Skills; Counselling; Creative Technologies; Digital Engagement; Inclusive Society; International Development; International Integration